Revival of Islam through Tajdid (Renewal) and Islah (Reform) tendencies in the post-communist Albania - Shehu, Fatmir Mehdi; Zejno, Bukuri (Bolgar Islamic Academy, 2019)
This article examines the revival of Islam in Albania through Tajdid (renewal) and Islah (reform) tendencies carried out by the Albanian Muslim Community and Muslim intellectuals, after the fall of the Communist System, in 1990s. The study intends to show the role of Tajdid and Islah activities in the restoration of Islam in the post-communist Albania. The significance of this research lies in its highlights of the renewal process of Islam in Albania within the first ten years after the fall of communism. This paper starts with a brief introduction on Albanians and their religious identity and continues with the discussion of: (1) the main factors leading to Tajdid and Islah in post-communist Albania, (2) the restoration of the Islamic educational institutions and the places of worship, and (3) the reformation of Muslim’s intellect, identity and belongingness. Descriptive and analytical methods are utilized. The analysis of this study adds new insights to the exiting literature on Tajdid and Islah tendencies for the revival of Islam in Albania.